Trait Empathy associated with Agreeableness and rhythmic entrainment in a spontaneous movement to music task: Preliminary exploratory investigations - Bamford, JMS; Davidson, JW (SAGE Publications, 2017)
The simulation theory of empathy suggests that we use motor processing to empathise, through modelling the actions of others. Similarly, research into embodied music cognition posits that music, particularly musical rhythm, is perceived as a motor stimulus. In both cases, the human Mirror Neuron System (MNS) is put forward as a potential underlying mechanism. If this is the case, some overlap may exist between the ability to empathise with others, and the ability to perceive rhythm in music. The present study investigated this relationship indirectly, through the study of individual differences in Trait Empathy and rhythmic entrainment. Undergraduate students (N = 237) completed a questionnaire battery including the EQ-Short, BFAS and questions about musical and dance experience. A relationship was observed between Agreeableness on the BFAS and the EQ-Short (r =.554). Tests on a controlled sample of these participants (n = 11) found a relationship between Trait Empathy and performance on a rhythmic entrainment task, involving spontaneous movement to a musical stimulus (r τ = -.686). A novel measure of rhythmic entrainment was used, assessing each participant on the time taken to re-establish entrainment following an abrupt change in tempo. The findings suggest that Empathy and rhythmic entrainment may utilise similar brain regions. These regions may also be associated with the MNS, although neuroimaging data would be required to confirm this. Qualitative observations of the participants’ responses to the various musical stimuli were also recorded, and may inform future study. Furthermore, the observed relationship between Agreeableness and Trait Empathy may have implications for how these personality constructs are treated in the literature.